Pengembangan Budidaya Cabai Hidroponik Berbasis Greenhouse untuk Mendukung Produksi Berkelanjutan - Rabbani Gadhah Kun Atha; Putri Salwa Zanjambila; Tiara Levana; Ahmad Fauzi Inu Kertopati; Nisrina Hamidah; Iva Iryana Kaban; Frida Mutia Sari; Nasywa Nurayudya Irawan; Muhammad Farrel Raya Syamsuddin; Agief Julio Pratama; M. Iqbal Nurulhaq; Ririh Sekar Mardisiwi; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2026)
Chili pepper (Capsicum annuum L.) is recognized as one of the horticultural commodities with significant economic value and an important contribution to food security in Indonesia. However, conventional cultivation practices still face various challenges, including limited land availability, climate uncertainty, and disturbances from plant pests and diseases. These conditions highlight the need for the implementation of innovative technologies to improve production efficiency while maintaining yield stability. One approach that has been increasingly developed is the hydroponic system, a cultivation technique that does not rely on soil as a growing medium but instead utilizes nutrient solutions as the primary source of essential elements. This article aims to examine various aspects of hydroponic chili cultivation, including the roles and benefits of the plant, different types of hydroponic systems, abiotic and biotic stress factors, and cultivation management strategies. Based on the review conducted, hydroponic systems, when supported by optimal nutrient management and environmental conditions, are capable of enhancing both the yield and quality of chili plants. Therefore, the development of hydroponic-based chili cultivation is considered to have promising prospects as a solution to support sustainable agriculture in the future.